Atypical clinical features of children with central nervous system tumor: Delayed diagnosis and switch in handedness. Issue 9 (21st July 2016) - Yokoi, Kentaro; Yamaoka, Masayoshi; Miyata, Ichiro; Nonaka, Yuichiro; Yuza, Yuki; Kawata, Shoko; Akiyama, Masaharu; Yanagisawa, Takaaki; Ida, Hiroyuki
Abstract: Herein is described the cases of three children with central nervous system (CNS) tumor, who had switch in handedness occurring before diagnostic confirmation. Although the onset, age, tumor location, and histology were heterogeneous, the diagnosis of CNS tumor was delayed in all three patients. The present experience indicates that switch in handedness should be recognized as a sign of CNS tumor in pediatric patients, and which might prevent delay in diagnosis. Pediatricians should carefully examine such patients who present with some suggestive symptoms of CNS tumor, even when they are unusual, in order to make a timely and appropriate diagnosis.